2020
DOI: 10.1111/ibi.12898
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection of foraging male Great Snipes on floodplain meadows: importance of proximity to the lek, vegetation cover and bare ground

Abstract: Drainage of wetlands and agricultural intensification has resulted in serious biodiversity loss in Europe, not least in grasslands. Consequently, many meadow birds have drastically declined, and the habitats they select for breeding currently rely on land management. However, the selection of habitats maintained by agriculture may contribute to reduced fitness and thus remain maladaptive for individuals, which makes conservation challenging. An understanding of the relationships between species’ habitat select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Therefore, the occurrence of the Wood Snipe seemed to be largely driven by soil conditions and food density rather than vegetation variables. This reflects similar findings for the breeding Common Snipe (Gallinago gallinago) and Great Snipe (G. media), in which habitat selection and body condition are associated with certain soil conditions and higher food availability (Green et al 1990, Korniluk et al 2021, Witkowska et al 2022. However, unlike the Great Snipe, we did not find strong evidence of Wood Snipe selecting habitat with moderate vegetation height and density to avoid potential predators (Løfaldli et al 1992), even though predation attempts by raptors were observed in the field.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the occurrence of the Wood Snipe seemed to be largely driven by soil conditions and food density rather than vegetation variables. This reflects similar findings for the breeding Common Snipe (Gallinago gallinago) and Great Snipe (G. media), in which habitat selection and body condition are associated with certain soil conditions and higher food availability (Green et al 1990, Korniluk et al 2021, Witkowska et al 2022. However, unlike the Great Snipe, we did not find strong evidence of Wood Snipe selecting habitat with moderate vegetation height and density to avoid potential predators (Løfaldli et al 1992), even though predation attempts by raptors were observed in the field.…”
Section: Discussionsupporting
confidence: 87%
“…Owing to the very limited information on Wood Snipe ecology, we considered a range of terrain, vegetation, soil, and human disturbance variables noted to be important to the habitat selection of other snipe species (Table 1) (Hoodless et al 2007, Mongin 2006, Korniluk et al 2021, Løfaldli et al 1992). At each site, we recorded elevation, slope aspect, and grade, as well as soil variables including moisture and penetrability.…”
Section: Methodsmentioning
confidence: 99%
“…In such hydrological circumstances, the remaining unflooded soil layer is thin, and earthworms are bound to occupy it in great densities. The Great Snipe uses the tactile foraging strategy, probing the soil and mud with a bill in search for prey (Cramp and Simmons 1983), and prefers feeding sites with high soil penetrability (Korniluk et al 2020). This parameter relies on the hydrological conditions of the meadow, as higher soil moisture can cause the top layer of the soil to become easier to penetrate (Armstrong 2000;Milsom et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, males must rely on abundant prey available at feeding sites on their breeding grounds, as breeding display constrains the replenishment of energetic resources by foraging during the day. The location of the Great Snipe leks is determined by the proximity of such rich feeding sites, especially with easily accessible and abundant earthworms Lumbricidae that compose 90% of the diet in this species (Løfaldli et al 1992;Kålås et al 1997;Korniluk et al 2020). Hence, it is possible, that the availability of high quality food such as earthworms determines the body condition of lekking birds.…”
Section: Introductionmentioning
confidence: 99%
“…We test whether invertebrates decline with increasing land use intensity, which would support the hypothesis that intensive farming practices are a key driver of invertebrate prey. We also examine whether and how invertebrates are affected by soil moisture content, a key variable for many wader species as it affects the ability of adult birds to probe the soil for invertebrate prey (Korniluk et al, 2021;Smart et al, 2006;Struwe-Juhl, 1995) and known to influence vegetation productivity (Heisler-White et al, 2009).…”
Section: Introductionmentioning
confidence: 99%